2017
DOI: 10.4274/jtgga.2016.0211
|View full text |Cite
|
Sign up to set email alerts
|

Urinary fistula-A continuing problem with changing trends

Abstract: Objective:Urinary fistula is a distressing complication after difficult vaginal deliveries, obstetric, and gynecologic surgeries. The present study describes a single center’s experience in the management of urinary fistula at a tertiary care hospital. It was performed to analyze the etiology of genitourinary fistula, to assess the outcome after surgical repair, and to determine the changing trends in the etiology and management of urinary fistula.Material and Methods:This retrospective study was conducted ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…The age of the subjects in this study ranged from 13-55 years with a mean of 28±11.1 years. This is similar to the findings of Kumar et al, Karateke et al and Amitava et al [12][13][14] This age range is within the child-bearing age of women as well as the age when obstetric and gynaecologic surgeries are most commonly performed. The youngest patient in this study was 13 years at the time of presentation.…”
Section: Discussionsupporting
confidence: 91%
“…The age of the subjects in this study ranged from 13-55 years with a mean of 28±11.1 years. This is similar to the findings of Kumar et al, Karateke et al and Amitava et al [12][13][14] This age range is within the child-bearing age of women as well as the age when obstetric and gynaecologic surgeries are most commonly performed. The youngest patient in this study was 13 years at the time of presentation.…”
Section: Discussionsupporting
confidence: 91%
“…An Indian study conducted from 2007 to 2013 reported that 39% of genitourinary fistulae were iatrogenic . A further study, conducted from 2011 to 2015 in India, reported that 65% of fistula cases were iatrogenic . Similarly, urogenital fistula studies conducted in Pakistan over various years have shown a gradual rising trend in iatrogenic fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Patients presented with symptoms for a median duration of 8 months. 13 They also classified fistula as simple and complicated based on characteristics of fistula, such as number, site, size, urethral involvement, scarring of tissue, and number of previous repairs. Simple fistulae were present in 55.0% women and 45.0% had complicated fistulae.…”
Section: Discussionmentioning
confidence: 99%